Modified Cenospheres as an Adsorbent for the Removal of Disperse Dyes. (23rd March 2015) - Tiwari, Markandeya; Shukla, S. P.; Mohan, D.; Bhargava, D. S.; Kisku, G. C.
Abstract : The main objective of this investigation was to use modified cenospheres for the removal of disperse blue 79:1 (DB) and disperse orange 25 (DO) dyes from aqueous solution by batch adsorption process under different conditions (pH, adsorbent dose, adsorbate concentration, agitation speed, contact time, and temperature). Modified cenosphere was capable of removing up to 78% of DB and 81% of DO dyes from aqueous solutions of 40 mg/L dyes concentration. The investigated data was explained by the Langmuir isotherm. The experimental data were found to follow the pseudo-second-order kinetic model. The results of this study suggested that modified cenospheres could be used as a low-cost alternative to expensive adsorbents like activated carbon in wastewater treatment for the removal of disperse dyes.